TINDAK TUTUR ILOKUSI SANDIAGA UNO DALAM TALKSHOW MATA NAJWA - Prihatin, Yulianah (STKIP PGRI Jombang, 2021)
The purpose of this article is to find out the illocutionary speech acts of Sandiaga Uno in the mata najwa talk show in TRANS 7 based on the form and type. The data obtained by the author comes from the utterances spoken by Sandiaga Uno in the Mata Najwa talk show on TRANS 7 which is re-aired on Najwa Shihab's Youtube channel April 15, 2021. The author collects data using listening and note-taking techniques. A speech act is an utterance that contains action as a functional unit in communication that considers aspects of the speech situation. Speech acts are classified into three, namely locutionary speech acts, illocutionary speech acts, and perlocutionary speech acts. In this article, the writer analyzes the illocutionary speech acts. Illocutionary speech acts are speech acts that are usually interpreted with explicit performative sentences. Based on the results of data analysis, it can be concluded that the forms of illocutionary speech acts obtained are declarative and imperative forms. While the types of illocutionary speech acts obtained are assertive, directive, and expressive.